Sistem Informasi Geografis Berbasis Web Pemetaan Lokasi Klinik Kecantikan di Baturaja - Agatha, Selvia Karina; Rizki, Tirta Amalia Sari; Cahyani, Keysha Shinta Dwi; Pujianto, Pujianto (Indo-MathEdu Intellectuals Journal, 2026)
Mapping of beauty clinic locations in Baturaja is not yet available in a digital form that is easily accessible to the public, making it difficult for users to find the nearest clinic and obtain the service information they need. This study aims to develop a web-based Geographic Information System (GIS) that presents the distribution of beauty clinic locations in the Baturaja area in an informative and interactive manner. The research methods used include collecting clinic location data through observation and documentation, system design, and application development using web technology and digital maps with the integration of each clinic's geographical coordinates. The results of the study show that the developed GIS is capable of displaying a map of the distribution of beauty clinics, detailed clinic information including addresses, services, and contacts, as well as a user location search feature. Thus, this system can help the public access beauty clinic information quickly, precisely, and accurately